Determination of Optical and Morphogeometric Properties of Forastero Cacao Seeds from Various Harvests (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Cacao (Theobroma cacao L.) is one of the most representative crops worldwide, with its fruit being in highest demand. Determining the optical and morphogeometric properties of cacao seeds is essential for evaluating grain quality criteria. Therefore, 300 g of fermented and dried beans from different harvest times were obtained from the Vijagual village, in the municipality of Bucaramanga. The sampling was random, selecting 20 experimental units per harvest and applying a univariate statistical analysis using the median and interquartile range. Subsequently, a bivariate analysis was performed using the non-parametric Mann-Whitney U test.The color component values were: L* 29.67 (28.18-33.73), a* 11.25 (9.99-12.54), and b* 9.07 (8.01-10.65). The physical measurements of the beans were: weight 1.26 g (1.10-1.48), length 23.72 mm (22.36-24.92), width 12.47 mm (11.56-13.54), thickness 7.75 mm (6.13-8.53), arithmetic diameter 14.62 mm (13.94-15.35), surface area 13.18 mm² (12.35-14.40), volume 1.5 ml (1.0-2.0), density 0.91 g/ml (0.75-1.16), and length/thickness ratio 3.11 (2.77-3.62).Additionally, significant differences were found when comparing cacao seeds from different harvest times in the color variables for chromaticity a*, weight, length, width, diameter, and surface area. It is concluded that these physical characteristics of cacao beans could be used to categorize quality control and process parameters.
Keywords: Theobroma cacao L; physical indexes; seeds; crops; variety